A Competitive Perspective on Internet Explorer - Davis, Steven J; Murphy, Kevin M (American Economic Review, 2000)
Microsoft's Internet Explorer (JE) technologies are included in Windows at no separate charge. Versions 1 and 2 of IE functioned as add-on features in Windows 95. They were not tightly integrated into Windows and did not make applications programming interfaces available to other software. Over time, IE became increasingly integrated into Windows, sharing code with other Windows features and supplying processing services to other operatingsystem components and to software applications. In addition to distribution as part of Windows, Microsoft has routinely offered free IE distribution and upgrades through other channels. Microsoft has also compensated internet access providers (IAP's) and internet content providers (ICP' s) for their efforts to promote the use and distribution of IE. Despite IE's no-revenue track record and assurances of free availability in the future, Microsoft spends large sums developing and promoting IE. One interpretation of these (and other) facts holds that Microsoft unlawfully tied the browsing functionality of IE to Windows 95 and 98 for anticompetitive purposes. This view rests on the premise that a non-Microsoft web browser could evolve into a substitute for Windows or promote potential substitutes. Of course, the emergence of a substitute would erode the profitability of Windows. Hence, according to this view, Microsoft sought to preclude or forestall the emergence of alternative software platforms by tying its own web browser to Windows and by entering into promotional agreements that raise costs for rival web browsers. As an alternative to this view, we offer a pro-competitive perspective on Microsoft's behavior with respect to IE. Our perspective resonates with several other aspects of Microsoft's behavior as well. It also carries important implications for the connection between market structure and consumer welfare.